PERFIL LIPIDICO EN PACIENTES RENALES CRONICOS HEMODIALIZADOS - Guerra de Muñoz, Martha; Departamento de Química, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
In the present work sorne biocherrlical blood pararneters were rnesured in fifty patients on chronic hernodialysis frorn the University Hospital La Samaritana. · The lipid profile included cholesterol, triglycerides, LDL, VLDL, HDL, and protein B. The patients were classilled using the Fredrickson's scale. The statistical analysis using Student's -t- test, showed statistical signillcant differences bety¡reen control and hernodyalisispatients.